Heat stress increases immune cell function in Hexacorallia - Eliachar, Shir; Snyder, Grace Ann; Barkan, Shany Klara; Talice, Shani; Otolenghi, Aner; Jaimes-Becerra, Adrian; Sharoni, Ton; Sultan, Eliya; Hadad, Uzi; Levy, Oren; Moran, Yehu; Gershoni-Yahalom, Orly; et al. (Frontiers in Immunology, 2022)
Climate change induced heat stress has increased coral bleaching events worldwide. Differentially regulated immune genes are one of the primary responses to heat stress suggesting that immune activation is critical. However, the cellular immune mechanisms of coral bleaching is currently unknown, and it is still not known if the immune response documented during heat stress is a consequence of bleaching or is directly caused by the heat stress itself. To address this question, we have used two model system sea anemones (Order: Actiniaria): Exaiptasia diaphana and Nematostella vectensis. E. diaphana is an established sea anemone model for algal symbiont interaction, while N. vectensis is an established sea anemone model that lacks the algal symbiont. Here, we examined the effect of increased temperature on phagocytic activity, as an indication of immune function. Our data shows that immune cell activity increases during heat stress, while small molecule pinocytosis remains unaffected. We observed an increase in cellular production of reactive oxygen species with increasing temperatures. We also found that the cellular immune activity was not affected by the presence of the Symbiodiniaceae. Our results suggest that the immune activity observed in heat-stress induced bleaching in corals is a fundamental and basic response independent of the bleaching effect. These results establish a foundation for improving our understanding of hexacorallian immune cell biology, and its potential role in coral bleaching.